Do differences make a difference? Understanding the dynamics of diversity in university community engagement workgroups - A Manaf, Aini Maznina; Ahmad, Zeti Azreen; Tengku Mohd Azzman, Tengku Siti Aisha (2020)
Community Engagement is prevalent in universities nowadays. Ideally, involvement in community engagement requires one to possess a strong teamwork spirit and skills to successfully achieve its goals. Addressing the issue of diversity in a team at workplace is crucial in the enhancement of teamwork spirit. Increasing demographic changes in organisations require people of different backgrounds to work together on a daily basis. As a result, it is common for groups and teams in organisations to be composed of members of different backgrounds. In a higher educational institution, working with academics of various disciplines in a community engagement projects are common. However, little is known on the diversity experiences of academics who are involved in university community engagement (UCE) projects. As such, this study aims to explore how academics’ diversity in UCE teams promotes towards positive or negative working experiences in community engagement group projects. This study employed qualitative methodology. Interviews with researchers involved in community engagement projects of a university in Malaysia were carried out.